1948
DOI: 10.1107/s0365110x48000867
|View full text |Cite
|
Sign up to set email alerts
|

The crystal structure of hexagonal barium titanate

Abstract: The crystal structure of hexagonal barium titanate has b~en determined by X-ray methods. The unit cell, which contains six units of BaTiOs, ha: %= 5.735 A. and co= 14.05 A. In the space group C6Jmmc all the ions occur at special positions: 2 Ba at (b), 4 Ba at (f), 2 Ti at (a), 4 Ti at (f), 6 O at (h), and 12 O at (k). The structure is built up of six close-packed layers of Ba and O ions, each layer consisting of one Ba to three O ions, having the packing sequence ABCACB. The Ti ions are located in the oxygen … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
95
0
4

Year Published

1959
1959
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 258 publications
(107 citation statements)
references
References 2 publications
7
95
0
4
Order By: Relevance
“…• in Ba(Ti0.gsPt0.12)O3 (Fischer & Tillmanns, 1981 (Burbank & Evans, 1948) and 14.023 (1)A (Fischer & Tillmanns, 1981) found in Ba(Ti,Pt)O3 compounds.…”
Section: Commentmentioning
confidence: 99%
See 1 more Smart Citation
“…• in Ba(Ti0.gsPt0.12)O3 (Fischer & Tillmanns, 1981 (Burbank & Evans, 1948) and 14.023 (1)A (Fischer & Tillmanns, 1981) found in Ba(Ti,Pt)O3 compounds.…”
Section: Commentmentioning
confidence: 99%
“…The crystal structure of hexagonal BaTiO3 was originally determined by Burbank & Evans (1948), using crystals synthesized by Matthias (1948) that had a light amber colour, attributed to dissolved platinum from the reaction vessel (Dickson, Katz & Ward, 1961;Tillmanns, • Hofmeister & Baur, 1985). The hexagonal BaTiO3 structure can be obtained by the addition of small amounts of other octahedral cations (Dickson, Katz & Ward, 1961).…”
Section: Commentmentioning
confidence: 99%
“…Erchak et al [3], reported the compound BaFe02.62 (BasFei + Fe~+ 02 1) which was thought to be a c ubic perovskite (a= 8.05 .A). Subsequently, Malinofsky and Kedesdy [4] showed that this phase is not cubic, but is actually analogous to the hexagonal polymorph of BaTi03 [5] with a = 5.68 ,, .A and c = 13.86 .A. They also reported a tetragonal perovskite polymorph, admixed with the hexagonal form, with a=3.98 .A and c=4.01 .A.…”
Section: Introductionmentioning
confidence: 96%
“…So far the crystal structures of Ba2TiO4 (Bland, 1961), cubic BaTiO3 (Megaw, 1947), hexagonal BaTiO3 (Burbank & Evans, 1948), BaTi205 (Harrison, 1956), BaTi409 (Lukaszewicz, 1957) and BaTisOll (Tillmanns, 1969) have been described. Rase & Roy (1955) report another compound in this system of composition BaTi307 and two more are mentioned by Kwestroo (1960): BazTisO~z and Ba2Ti9020.…”
Section: Introductionmentioning
confidence: 99%